Rabies in the big fruit-esting bat Artibeus lituratus from Botucatu, Southeastern Brazil - Langoni, H. [UNESP] (2005)
Rabies is a viral disease of mammals transmitted through the bite of a rabid animal. A frugivorous adult male bat, Artibeus lituratus, family Phyllostomidae, was diagnosed as positive to rabies by direct immunofluorescence (DIF) and mouse inoculation test (MIT) of the bat's brain, both performed at the School of Veterinary Medicine and Animal Husbandry - FMVZ, UNESP, Botucatu, São Paulo State, Brazil. The animal collided with the window of a commercial establishment in the urban area during the day. With regard to DIF, a high amount of Negri bodies of several sizes was observed in the brain. The spleen and right kidney presented some Negri bodies too. In relation to MIT, the mice presented paralysis in the 7th day, and died in the day after with several characteristic small bodies. The reverse transcriptase-polymerase chain reaction (RT-PCR), followed by hemi-nested RT-PCR (hnRT-PCR) resulted in an amplification of fragments from the bat's brain viral RNA, 432bp in RT-PCR, and 274bp in hnRT-PCR, confirming the diagnosis. Therefore, the hnRT-PCR and DIF have good sensitivity and specificity, providing and confirming the diagnosis of the clinical samples in a short period of time.